TINDAK TUTUR EKSPRESIF DALAM NOVEL PERAHU KERTAS KARYA DEWI LESTARI - Tilova, Kristine Santa; Sinaga, Mangatur; Rumadi, Hadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was titled Expressive Speech in Dewi Lestari's Novel Kertas Boat. This study aims to analyze expressive speech acts in Dewi Lestari's novel paper boat on the form and meaning contained in the novel. The method used is descriptive analysis method with a qualitative approach. In this study, the authors used two techniques, namely documentation or library techniques and data collection techniques by reading Dewi Lestari's novel KapalKertas as a source of data as a whole, marking and underlining each speech in accordance with the form and meaning of expressive speech acts, classifying forms and meanings expressive speeches in Dewi Lestari's novel PerahuKertas, analyzing and describing the form of expressive speech acts and the meaning of expressive speech acts in Dewi Lestari's paper boat novel. The results of this study indicate that the first form of expressive speech acts in Dewi Lestari's paper boat novel, the form of this study amounts to 123 data, from the results of the research the authors found in the form and meaning of expressive speech acts in the form of expressive speech acts in the form of asking sorry consists of twenty-five data, states congratulations consists of fourteen data, say greetings consist of seven data, say thank you consists of thirty one data, pleasure consists of five data, receive consists of six data, refuse consists of seven data , forgiveness consists of five data, blame consists of six data, praise consists of seventeen data. The two meanings of expressive speech acts in Dewi Lestari's paper boat novel (a) the meaning of forgiveness / regret, (b) the meaning of salvation, (c) the meaning of greeting and respect, (d) the meaning of thanks, (e) the meaning of happy, satisfied, and fondness, (e) meaning of getting, taking (f) meaning of rejecting / not, (g) meaning of good, (h) Meaning of seeing, (i) meaning of waw, wow.Key Words: Expressive Speech Acts, Expressive Speech Acts, The Meaning Of Expressive Speech Acts.